IMPLEMENTATION OF PROJECT BASED LEARNING MODEL FOR IMPROVING STUDENTS LEARNING OUTCOMES OF ADVANCED MACHINING ENGINEERING IN UNIVERSITAS SARJANAWIYATA TAMANSISWA - Setuju Setuju (VANOS Journal of Mechanical Engineering Education, 2017)
This research was conducted to improve learning outcomes through project-based learning model in the course of advanced machining in the department of Mechanical Engineering Education. This research was motivated by the low students learning outcomes in the advanced machining course, whereas the results of the study subjects was the vital thing for the students who will have production expertise. The research method was Classroom Action Research (CAR) with Kemmis and Mc Taggart model, by pointing in cycle, and consists of four stages: planning, implementation, observation, and reflection. Subjects were student of Mechanical Engineering Education production option that follows the advanced machining course for academic year 2014/2015. Data were collected by instruments such as observation sheet during the action takes place, the observation sheet practical activities for learning outcomes. Data was analyzed using quantitative descriptive. Project Based Learning (PjBL) model can improve learning outcomes in affective and psychomotor abilities of students. The increase in affective reaches 9.41 and psychomotor abilities enhancement from the first cycle to the second cycle reaches 6.6.